Legal Certainty on Sanction of Regional Regulation of Bandung City No. 7 of 2018 on Cultural Heritage Management Regarding The Renovation of Cultural Heritage in Bandung City - Steven Jonathan Winardi; Christin Septina Basani (Veteran Law Review, 2022)
Historical buildings that spread out all over Bandung City become silent witness of the city’s establishment until the present day. Some of them currently still last in the good shape and well-maintained, while the others fall apart by modernization. It is not infrequently happening that renovation of the old building becoming the new building done without neither license nor regulation. This research aims to analyze and understand the legal sanction related to renovation of historical building as a part of cultural heritage in Indonesia, specifically Bandung City, West Java. The purpose of this research is to engage all elements of society’s concern and involvement in cultural heritage preservation. The method of this research is library research as a research in literature or an activity to compile information relevant to topic or object of research and received from books, scientific paper, thesis, dissertation, encyclopedia, internet and other resources. The research shows the result that the consequence of a construction being established as cultural heritage is maintaining the values of history, culture, knowledge, religion, even architecture. People, especially in Indonesia worry about cultural heritage construction because the citizen minds that the construction cannot be modified, tumbled down or hard to sell.